Factors Associated With The Incidence Of Temper Tantrums In Preschool Children (Aged 3-6 Years) At Paud Putri Ayu Posyandu Melur I And Ummi Peduli Bengkulu Year 2024 - Lestari. A, Sela Nova; Aprianti, Delta; Pebriani, Emi (Universitas Dehasen Bengkulu, 2025)
Temper tantrum is a problem that often occurs in pre-school children. Factors that influence the occurrence of temper tantrums are parenting, parental communication, and work. The purpose of this research is to determine the factors associated with the incidence of temper tantrums. The method in this research is descriptive quantitative research with a cross sectional approach. The place of this research is in two places, namely in Paud Putri Ayu and Paud Ummi Peduli Bengkulu The population in this study were all preschool children (aged 3-6 years). The sample in this study used a total sampling technique totalling 43 respondents. Data collection using primary data by distributing questionnaires of temper tantrums, parenting patterns, parental communication, and employment. The results showed that almost half of 19 (44.2%) respondents who experienced temper tantrums, a small proportion of 16 (37.2%) respondents with authoritarian parenting, a small proportion of 17 (39.5%) respondents who had ineffective parental communication, almost half 18 (41.9%) respondents with working parents. There is a relationship between parenting factors, parental communication factors, and work with the incidence of temper tantrums in preschool children (aged 3-6 years) at PAUD Putri Ayu Posyandu Melur I and Ummi Peduli Bengkulu 2024. The conclusion in this study is that communication, parenting and parental work can affect the occurrence of temper tantrums. The suggestion in this study is that people do good communication, democratic parenting to reduce the incidence of temper tantrums in preschool children.